2017
DOI: 10.1021/acs.cgd.7b00096
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Polymer Molecular Weight on the Crystallization Behavior of Indomethacin Amorphous Solid Dispersions

Abstract: The influence of the molecular weight of polyvinylpyrrolidone (PVP) on the molecular mobility and physical stability of indomethacin (IMC)–PVP solid dispersions was investigated over a wide temperature range in the supercooled state. As the polymer molecular weight increased, there was a decrease in molecular mobility as evident from the longer α-relaxation times. Inhibition of IMC crystallization also increased as a function of polymer molecular weight. The extent of H-bonding interaction between drug and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 32 publications
3
44
0
Order By: Relevance
“…In this regard, it is important to emphasize that it has been shown that the polymer M w does not influence the equilibrium solubility of the drug in the polymer at ambient temperature [14]. On the other hand, it has been shown that an ASD comprising the drug IND together with PVP of a higher M w (K30) showed increased physical stability as a result of overall reduced molecular mobility compared to an ASD with PVP of lower M w (K12) [8]. In other words, whilst a higher M w is more efficient at preventing crystallization, it also requires longer milling times to achieve a fully amorphous solid dispersion.…”
Section: Pharmaceutics 2020 12 X For Peer Review 4 Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, it is important to emphasize that it has been shown that the polymer M w does not influence the equilibrium solubility of the drug in the polymer at ambient temperature [14]. On the other hand, it has been shown that an ASD comprising the drug IND together with PVP of a higher M w (K30) showed increased physical stability as a result of overall reduced molecular mobility compared to an ASD with PVP of lower M w (K12) [8]. In other words, whilst a higher M w is more efficient at preventing crystallization, it also requires longer milling times to achieve a fully amorphous solid dispersion.…”
Section: Pharmaceutics 2020 12 X For Peer Review 4 Ofmentioning
confidence: 99%
“…In this regard, it has been shown that increasing the polymer chain length/molecular weight (M w ) increases the physical stability of an ASD of indomethacin (IND) in polyvinylpyrrolidone (PVP) as a result of overall reduced molecular mobility [8]. Furthermore, the M w of the polymer has also been shown to affect the dissolution rate and performance of the drug from an ASD.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, polymers with a high T g may cause difficulties in processing. For instance, the use of such high T g polymers in hot melt extrusion (HME), one of the most popular preparation methods for ASDs, usually requires the aid of plasticizers, which in turn will reduce the systemic T g [30,31]. Polymers that interact with APIs through hydrogen bonds and ionic interactions have been shown to restrict the molecular mobility of ASD systems in addition to their contribution in thermodynamic stability [11,32].…”
Section: Kinetic Factors On the Physical Stability Of Asdsmentioning
confidence: 99%
“…In experiments, the structural relaxation time, τ α , is typically measured by the broadband dielectric spectroscopy (BDS) technique [14][15][16]. The global atomic rearrangement causes a prominent, broad, and asymmetry α-peak on the dielectric loss spectra.…”
Section: Introductionmentioning
confidence: 99%
“…The global atomic rearrangement causes a prominent, broad, and asymmetry α-peak on the dielectric loss spectra. From these, one can capture a dramatic growth of τ α upon isobaric cooling or isothermal squeezing [14][15][16]. When τ α reaches 10 2 s, amorphous pharmaceutical systems undergo the glass transition and fall out of equilibrium.…”
Section: Introductionmentioning
confidence: 99%